The EU's consular protection policy from the administrative law perspective - Csatlós, Erzsébet (Central European Public Administration Review, 2020)
The European Administrative Space has grown into a multi-level administrative structure characterised by the horizontal and vertical cooperation of all its levels. The sole executive responsibility of Member States' administrations has been substituted by cooperative networks of direct and indirect level authorities due to the growing number of composite procedures. Thus, consular protection policy has evolved from an intergovernmental regime to a special European administration field. The multi-level institutionalisation of the execution and evaluation of Euro' pean policies is a coherent system compared to the obligation de résultat of the Member States once associated with the implementation of the acquis. Therefore, the article examines what constitutes European administration in this and other policy fields and what represents its structural and procedural law sides. The EU consular protection policy as such is a unique policy at the crossroads of international law, domestic law and different level of EU law. Europeanisation of a certain policy often means a sort of harmonisation of substantial law; however, in case of consular protection, it is not targeted. Consular protection policy is Europeanised in structural and procedural aspects under the auspices of fundamental right protection and ends up in the creation of the European administration for the policy. The article thus highlights the process of establishing European administration and calls attention to possible problems of legal application while offering theoretical bases to eliminate them.
Keywords: administrative cooperation; consular assistance; EU citizenship; EU law; European administration; soft law